The Influence of Pop-up Card Media on Students' Learning Abilities in Science Learning at the Kampung Bharu Malaysia Learning Center - Rizki Diah Ayu Azhara; Ismail Saleh Nasution (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to determine the effect of using Pop up card media on students' learning abilities in science learning at the Kampung Bharu Learning Center, Malaysia. The background of this study is based on the low learning abilities of students caused by the lack of variation and effectiveness of learning media, so that learning tends to be abstract and less interesting. This study uses a quantitative approach with a quasi-experimental design in the form of One Group Pretest-Posttest Design. The subjects of the study were all 9 students of grade IV of the Kampung Bharu Learning Center, Malaysia, with a sampling technique using saturated sampling. The research instrument was a learning ability test given before (pretest) and after (posttest) treatment. Data were analyzed using the Shapiro-Wilk normality test and paired sample t-test hypothesis test with the help of SPSS version 25. The results showed that the average value of students' learning abilities increased after the application of Pop up card media, from an average pretest value of 10.11 to an average posttest value of 11.44. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.001, which is smaller than the significance level of 0.05, so H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the use of Pop-up card media has a significant effect on students' learning abilities in science learning. Pop-up card media has been proven to be able to present material visually and concretely, increase learning motivation, and encourage active student involvement during the learning process.